Inequity in the face of success: understanding geographic and wealth-based equity in success of facility-based delivery for under-5 mortality reduction in six countries - Jovial Thomas Ntawukuriryayo; Amelia VanderZanden; Alemayehu Amberbir; Alula Teklu; Fauzia Akhter Huda; Mahesh Maskey; Mohamadou Sall; Patricia J. Garcia; Raj Kumar Subedi; Felix Sayinzoga; Lisa R. Hirschhorn; Agnes Binagwaho (BMC, 2024)
Abstract Background Between 2000-2015, many low- and middle-income countries (LMICs) implemented evidence-based interventions (EBIs) known to reduce under-5 mortality (U5M). Even among LMICs successful in reducing U5M, this drop was unequal subnationally, with varying success in EBI implementation. Building on mixed methods multi-case studies of six LMICs (Bangladesh, Ethiopia, Nepal, Peru, Rwanda, and Senegal) leading in U5M reduction, we describe geographic and wealth-based equity in facility-based delivery (FBD), a critical EBI to reduce neonatal mortality which requires a trusted and functional health system, and compare the implementation strategies and contextual factors which influenced success or challenges within and across the countries. Methods To obtain equity gaps in FBD coverage and changes in absolute geographic and wealth-based equity between 2000-2015, we calculated the difference between the highest and lowest FBD coverage across subnational regions and in the FBD coverage between the richest and poorest wealth quintiles. We extracted and compared contextual factors and implementation strategies associated with reduced or remaining inequities from the country case studies. Results The absolute geographic and wealth-based equity gaps decreased in three countries, with greatest drops in Rwanda - decreasing from 50 to 5% across subnational regions and from 43 to 13% across wealth quintiles. The largest increases were seen in Bangladesh - from 10 to 32% across geography - and in Ethiopia - from 22 to 58% across wealth quintiles. Facilitators to reducing equity gaps across the six countries included leadership commitment and culture of data use; in some countries, community or maternal and child health insurance was also an important factor (Rwanda and Peru). Barriers across all the countries included geography, while country-specific barriers included low female empowerment subnationally (Bangladesh) and cultural beliefs (Ethiopia). Successful strategies included building on community health worker (CHW) programs, with country-specific adaptation of pre-existing CHW programs (Rwanda, Ethiopia, and Senegal) and cultural adaptation of delivery protocols (Peru). Reducing delivery costs was successful in Senegal, and partially successful in Nepal and Ethiopia. Conclusion Variable success in reducing inequity in FBD coverage among countries successful in reducing U5M underscores the importance of measuring not just coverage but also equity. Learning from FBD interventions shows the need to prioritize equity in access and uptake of EBIs for the poor and in remote areas by adapting the strategies to local context.